Pengaruh Gawai Terhadap Perilaku Anak Usia Dini Di Kelurahan Winangun Satu Lingkungan Satu Kota Manado - Jenny Dengah (Peneliti.net, 2021)
In this digital era, who doesn't know gadgets, multifunctional devices that are used in everyday life not only as a means of communication but also as entertainment. Not only adults, gadgets are also used by children at an early age for entertainment or education. It was found that there were children who behaved aggressively, some were friendly, and even forgot the time to rest, bathe or eat. The formulation of the problem in this study: how are the social and emotional behaviors of early childhood users of gadgets in the Winangun Satu Subdistrict, Neighborhood One, Malalayang District, Manado City. The method used in this study is a qualitative method because it is more suitable for gathering information. In the process of collecting data researchers used interviews, observation and documentation. Data analysis techniques Miles and Huberman (1992:20) were used in this study starting from data collection, data reduction, data presentation and drawing conclusions and verification. The subjects in this study were 2 young children who were 3 and 5 years old who spent time with gadgets. The results of the study show that the social behavior of early childhood users of devices as follows: children tend to prefer to be alone and find it difficult to adapt to a new environment. Children have irritable emotions when their parents want to take the device and will also cry and rebel.